Investigation of construction waste material using multi criteria decision making method: a case study in Bhutan - Khameis Mohamed Al Abdouli; Mon Bdr Sinchuri; Nima Yoezer; Nima Pakhring; Anju Chhetri; Nimesh Chettri (Discover Applied Sciences)
Abstract Construction waste encompasses all of the leftover or unwanted materials, substances, and by-products that arise from constructing, renovating, or demolishing buildings, infrastructure, or other construction projects. Currently, there is a lack of systematic data on the most common types of construction waste in Bhutan. This research seeks to fill this critical knowledge gap by conducting a comprehensive analysis to identify the predominant types of construction waste in the Bhutanese and quantify it using multi-criteria decision analysis (MCDA). The images of wastes were collected from multifarious construction site from all the dzongkhags (district). Subsequently, questionnaire was designed and distributed to engineers for pair wise comparison. Using a fuzzy analytic hierarchy process, a MCDA technique was calculated to weight the scores for the factors like frequency in occurrence, environmental impacts, and recyclability. This comprehensive analysis resulted in a ranked list of waste according to their total performance scores, with wood identified as the most prevalent type of construction waste in Bhutan.